1995
DOI: 10.1021/bi00001a005
|View full text |Cite
|
Sign up to set email alerts
|

Human (MDR1) and Mouse (mdr1,mdr3) P-glycoproteins Can Be Distinguished by Their Respective Drug Resistance Profiles and Sensitivity to Modulators

Abstract: Possible functional differences between P-glycoproteins (P-gps) encoded by the human MDR1 and mouse mdr1 and mdr3 genes with respect to drug resistance profiles and sensitivity to known modulators have been investigated. For this, the three genes were introduced and overexpressed in the same cellular background, that of Chinese hamster LR73 ovary cells, and drug-resistant clones expressing comparable amounts of the corresponding P-gps were selected under the same conditions. Analysis of the specific drug resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 44 publications
4
76
0
Order By: Relevance
“…It is possible that axitinib is a substrate for canine P-gp and that the MDR1-MDCK and BCRP-MDCK cell lines used by Poller et al (2011) may contain higher levels of canine P-gp than our cell lines, resulting in the contrasting results between the two laboratories. Additionally, it was previously demonstrated that P-gp activity differs between species (Tang-Wai et al, 1995). This species-specific activity may account for the differences in axitinib efflux in the various systems.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that axitinib is a substrate for canine P-gp and that the MDR1-MDCK and BCRP-MDCK cell lines used by Poller et al (2011) may contain higher levels of canine P-gp than our cell lines, resulting in the contrasting results between the two laboratories. Additionally, it was previously demonstrated that P-gp activity differs between species (Tang-Wai et al, 1995). This species-specific activity may account for the differences in axitinib efflux in the various systems.…”
Section: Discussionmentioning
confidence: 95%
“…Obviously, the feasibility, safety, and efficacy of this procedure should be tested carefully in preclinical models and clinical practice. For example, differences between effects of placental P-gp on drug penetration into human and murine fetuses might arise from differences in substrate specificity between human MDR1 Pgp and murine Mdr1a and Mdr1b P-gp (38).…”
Section: Discussionmentioning
confidence: 99%
“…Early work demonstrated that cells transfected with Mdr1b were resistant to colchicine and doxorubicin whereas cells overexpressing Mdr1a were resistant to actinomycin D (Table 7) (Devault and Gros, 1990;Tang-Wai et al, 1995). In addition, MDR1-transfected cells were resistant to vincristine, colchicine, daunorubicin, doxorubicin, and actinomycin D (Schinkel et al, 1991;Tang-Wai et al, 1995).…”
Section: Multidrug and Toxin Extrusionmentioning
confidence: 99%